Bacterial steroid-17, 20-desmolase is a taxonomically rare enzymatic pathway that converts prednisone to 1, 4-androstanediene-3, 11, 17-trione, a metabolite that causes proliferation of prostate cancer cells. Issue 199 (May 2020) - Ly, Lindsey K.; Rowles, Joe L.; Paul, Hans Müller; Alves, João M.P.; Yemm, Camdon; Wolf, Patricia M.; Devendran, Saravanan; Hudson, Matthew E.; Morris, David J.; Erdman, John W.; Ridlon, Jason M.
Highlights: Host-associated bacteria are capable of converting cortisol to 11-oxy-androgens via steroid-17, 20-desmolase encoded by the desAB genes. Phylogenetics and sequence similarity network analysis of bacterial DesA and DesB. Bacteria encoding DesAB are capable of metabolizing both endogenous glucocorticoids and glucocorticoid drugs. The side-chain cleavage product of prednisone causes significant proliferation of prostate cancer cells (LNCaP). Abstract: The adrenal gland has traditionally been viewed as a source of "weak androgens"; however, emerging evidence indicates 11-oxy-androgens of adrenal origin are metabolized in peripheral tissues to potent androgens. Also emerging is the role of gut bacteria in the conversion of C21 glucocorticoids to 11-oxygenated C19 androgens. Clostridium scindens ATCC 35, 704 is a gut microbe capable of converting cortisol into 11-oxy-androgens by cleaving the side-chain. The desA and desB genes encode steroid-17, 20-desmolase. Our prior study indicated that the urinary tract bacterium, Propionimicrobium lymphophilum ACS-093-V-SCH5 encodes desAB and converts cortisol to 11β-hydroxyandrostenedione. We wanted to determine how widespread this function occurs in the human microbiome. Phylogenetic and sequence similarity network analyses indicated that the steroid-17, 20-desmolase pathway is taxonomically rare and located in gut and urogenital microbiomes. Two microbes from each of these niches, C. scindens and Propionimicrobium lymphophilum, respectively, were screened for activity against endogenous (cortisol, cortisone, and allotetrahydrocortisol) and exogenous (prednisone, prednisolone, dexamethasone, and 9-fluorocortisol) glucocorticoids. LC/MS analysis showed that both microbes were able to side-chain cleave all glucocorticoids, forming 11-oxy-androgens. Pure recombinant DesAB from C. scindens showed the highest activity against prednisone, a commonly prescribed glucocorticoid. In addition, 0.1 nM 1, 4-androstadiene-3, 11, 17-trione, bacterial side-chain cleavage product of prednisone, showed significant proliferation relative to vehicle in androgen-dependent growth LNCaP prostate cancer cells after 24 h (2.3 fold; P  <  0.01) and 72 h (1.6 fold; P < 0.01). Taken together, DesAB-expressing microbes may be an overlooked source of androgens in the body, potentially contributing to various disease states, such as prostate cancer.